The Effect of Livelihood Capital Accessibility on the Financial Security and Financial Well-being of Sheep Farming Households (Survey in Wanaraja Subdistrict, Garut Regency) - Yunasaf, Unang; Kuswaryan, Sondi; Suhendarsyah, Suhendarsyah (Jurnal Ilmu Ternak Universitas Padjadjaran, 2026)
This study analyzed the influence of livelihood capital accessibility on the financial security and financial well-being of sheep-farming households in Wanaraja Subdistrict, Garut Regency. A quantitative approach was used through a survey with organized interviews of 95 sheep farmers. The research variables include livelihood capital accessibility (X), financial security (Z), and financial well-being (Y). The livelihood capital accessibility construct was built as a Higher-Order Construct with five dimensions: human, natural, financial and physical capital. Data analysis used Partial Least Square Structural Equation Modeling (PLS_SEM) with a two-stage approach. The results evince that social capital are the most influential dimensions in forming livelihood capital accessibility, while human, natural, financial and physical capital are not significant. Structurally, accessibility of livelihood capital has a significant a significant influense on financial security and financial well-being of farmers is shaped not only by objective economic conditions but also by access to livelihood assets improved financial stability, it also seemed to create additional financial responsibilities that reduced the farmer’s sense of well-being.